Freedom to flourish: UK regulatory autonomy, recognition, and a productive economy - Shanker A. Singham; Radomir Tylecote; Victoria Hewson (Institute of Economic Affairs (IEA), 2018)
Withdrawal from the EU must mean regulatory autonomy for the United Kingdom - sovereignty over its regulations. This reflects the democratic mandate of the 2016 referendum and the 2017 manifesto commitments of the Conservative and Labour Parties, and will propel growth and competition in the economy. It is also necessary for the UK to be able to sign advanced trade agreements with countries around the world. The United Kingdom has a unique opportunity to use withdrawal from the EU to grow its economy and become considerably more productive. It is vital that nothing is done to take these benefits off the table. But for pro-competitive regulation, regulatory autonomy is vital. In her Lancaster House speech in 2017, the Prime Minister outlined that Brexit would mean legal independence through an end to European Court of Justice jurisdiction in the UK, and that the UK must be free to execute an independent trade policy, striking agreements with countries outside the EU, outside the Customs Union's Common External Tariff. In her speech at the Mansion House in March 2018, she stated that this meant our regulations would 'achieve the same outcomes' as EU law, but need not be identical. To deliver an independent trade policy and substantially more prosperous economy, the UK must have the ability to change its regulatory system from the EU's acquis when it seeks to do so, and when beneficial for trade agreements. A 30% reduction in regulatory distortions between key trading partners by 2034 could mean GDP up to 7.25% higher than it would otherwise have been. The UK must be able to deliver the following five points: 1) Autonomy for the UK to make its own regulation; 2) Autonomy for the UK to set its own standards; 3) Autonomy for a UK system of conformity assessment; 4) Unilateral recognition by the UK of EU regulations, standards, and its conformity assessment system; 5) Seek recognition by the EU of the UK's regulations, standards, and its conformity assessment system.
Keywords: L51; F42; F53; F55; F15; L50; L51; F42; F53; F55; F15; L50; 330